2001
DOI: 10.1172/jci10128
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ and Fas/FasL are required for the antitumor and antiangiogenic effects of IL-12/pulse IL-2 therapy

Abstract: Systemic administration of IL-12 and intermittent doses of IL-2 induce complete regression of metastatic murine renal carcinoma. Here, we show that overt tumor regression induced by IL-12/pulse IL-2 is preceded by recruitment of CD8(+) T cells, vascular injury, disrupted tumor neovascularization, and apoptosis of both endothelial and tumor cells. The IL-12/IL-2 combination synergistically enhances cell surface FasL expression on CD8(+) T lymphocytes in vitro and induces Fas and FasL expression within tumors vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
4
49
0
Order By: Relevance
“…In addition, implantation of POB UN0092 murine neuroblastoma cells (J.K. Stauffer et al, manuscript in preparation) 20 into syngeneic transgenic actin-GFP mice 21 results in the formation of tumors that are vascularized by green fluorescent hostderived vessels. Consistent with the mechanism of action by IL-12 in other preclinical models, [22][23][24] we have now validated the use of this model system by demonstrating that administration of IL-12 can potently inhibit the vascularization of POB UN0092 murine neuroblastoma tumors that have been established in actin-GFP mice. Counterstaining with DAPI provides tumor sections in which vessel density (green) as well as nuclear morphology (blue) in the vascular endothelial and tumor cell compartments can be directly evaluated and/or quantitated.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, implantation of POB UN0092 murine neuroblastoma cells (J.K. Stauffer et al, manuscript in preparation) 20 into syngeneic transgenic actin-GFP mice 21 results in the formation of tumors that are vascularized by green fluorescent hostderived vessels. Consistent with the mechanism of action by IL-12 in other preclinical models, [22][23][24] we have now validated the use of this model system by demonstrating that administration of IL-12 can potently inhibit the vascularization of POB UN0092 murine neuroblastoma tumors that have been established in actin-GFP mice. Counterstaining with DAPI provides tumor sections in which vessel density (green) as well as nuclear morphology (blue) in the vascular endothelial and tumor cell compartments can be directly evaluated and/or quantitated.…”
Section: Discussionsupporting
confidence: 70%
“…[22][23][24] We next validated that the model systems described previously could be used to investigate cytokine-induced alterations in the vascularization of neuroblastoma tumors. C57BL/6-TgN(ACTbEGFP)10sb mice bearing advanced 17-day established subcutaneous POB UN0092 neuroblastoma tumors were treated with IL-12 or vehicle alone as described in the Materials and Methods section.…”
Section: Antiangiogenic Effects Of Il-12 In C57bl/6-tgn(actbegfp)1osbmentioning
confidence: 91%
“…The relevant molecular mechanisms mediating cross-repressive interactions between cytokine-engineered MSCs and tumor growth and metastases should be involved in multiple aspects including: first, MSCs tend to travel to the same homing destination as the migrating cancer stem cell 26 with unusual abilities to migrate to oncogenetic or metastatic sites and directly attack tumors by contacting target cells and inhibiting their Akt activity; 12,22,27 then, the AdIL-12, which is hidden in the MSCs can evade the immune system surveillance and be well tolerated by the host without inducing an unacceptable immune response; after this, AdIL-12 can be localized to tumor microenvironments to express the cytokine gradually without interfering with other systems and, consequently, improve the pharmacokinetics of IL-12 and minimize the inherent toxic effects radically; subsequently, the target-specific expression of IL-12 would induce rapid destruction of established tumor-associated endothelial cells and regression of metastatic tumor cells via the Fas/FasL pathway as well as by inhibiting Akt phosphorylation. [28][29][30] The target-aimed biomolecules could promote downregulation of the VEGF receptor-3 signaling pathway or blockade of ligands VEGF-D to prevent any unestablished lymphatic endothelium from sprouting, 31,32 in a similar manner as has been revealed by the immunohistochemistry assay. However, blocking of VEGF receptor-3 signaling could only suppress tumor lymphangiogenesis and metastases to regional LNs but not to the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a metastatic murine renal carcinoma model, Wiggington et al demonstrated that IL-12/IL-2 combination enhances FasL expression on the CD8+ T cell surface, and tumor rejection was preceded by recruitment of CD8+ FasL+ cells in the tumor microenvironment, suggesting a complex interaction of IFN-c and Fas/FasL pathways in mediating the therapeutic effects of IL-12 (Wigginton et al, 2001). NK cells may indeed contribute to IL-12 action by bringing about tumor cell death both directly and indirectly, through damaging of the vasculature.…”
Section: From Ex Vivo Transduced Cells To In Vivo Gene Transfer: Inpumentioning
confidence: 99%